The Braveheart amphipod: a review of responses of invasive Dikerogammarus villosus to predation signals - Jermacz, Łukasz (PeerJ, 2018)
Predator pressure is a fundamental force driving changes at all levels of the community structure. It may protect native ecosystems from alien species. Therefore, resistance to diverse predators resulting from a universal anti-predator strategy seems crucial for invasion success. We present a comprehensive review of the responses of an invasive amphipod Dikerogammarus villosus to sympatric and allopatric predator signals. We summarize diverse aspects of the gammarid anti-predator strategy, including predator identification, morphological and behavioural adaptations, effectiveness of shelter use and resistance to indirect predator effects. The response of D. villosus is independent of predator species (including totally allopatric taxa), which assures the high flexibility of its predator recognition system. It has a harder exoskeleton and better capability of utilizing shelters compared to other gammarids, resulting in relatively high resistance to predators. Therefore, it can use predator kairomones as indirect food signals (sharing the diet with the predator) and follow the predator scent. This resistance may allow D. villosus to reduce the costs of its physiological responses to predators and sustain growth in their presence. This might facilitate invasion success by increasing its competitive advantage.